The importance of freshwater species to livelihoods in the Lake Victoria Basin - Sayer, C.A.; Akwany, L.O.; Kishe-Machumu, M.A.; Natugonza, V.; Omondi, R.; Kabuye, C.S. (IUCN Global Species Programme., 2018)
Freshwater biodiversity plays a significant role in supporting the livelihoods of human communities around the world, particularly of people in rural and poor communities. In the developing world, 56 million people are involved in small-scale freshwater fisheries and in Sub-Saharan Africa, fisheries are a key source of nutrition and income for much of the rural population (Béné et al., 2010). Additionally, the value of largescale fisheries and of other harvested freshwater species,primarily decapods, molluscs and plants, are important for rural communities across Africa, providing not only nutritional but medicinal, structural and cultural values, amongst others.
Keywords: Freshwater species; Livelihoods